Installation of Gravel in the Switchyard Area of the Substation with Dusty Sandy Soil Reduces Step Voltage and Touch Voltage - Janardana, IGN; Wijaya, I Wayan Arta (Journal of Electrical, Electronics and Informatics; Vol 8 No 1 (2024): JEEI (June 2024), 2025)
The thickness of the gravel layer in the substation area is often ignored, even though it can increase the resistance of the officers' feet. The gravel layer at the switchyard location must comply with IEEE Std 80-2013 standards. The aim of this research is to determine the thickness of gravel in the switchyard equipment grounding system on dusty sandy soil to eliminate the stress gradient between equipment and equipment, equipment and soil and the stress gradient on the ground surface itself. The method used in this research analysis is descriptive quantitative. The results show that with increasing thickness of gravel, the step voltage and touch voltage decreases but a gravel thickness of 15 cm has the best value.